The effect of key performance indicator (KPI) toward work-life balance - Siti Zakiah, Bt Abu Nain (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study is conducted to investigate the effect of KPI (key performance indicator) toward work life balance of employee in a public university in Pahang. The independent variable for this study is KPI (key performance indicator) While the dependent variable is Work-life balance. Questionnaire has been used as the method to collect data for this study. The respondent for this study is 100 employee from management line that randomly chosen for this research. The collected data been analyse by using the Statistical Package for Sosial Science Version 21.0 (SPSS version 21.0). The effect of KPI (key performance indicator) toward work-life balance has been test using the Pearson correlation analysis. The result show that there is a significant different between KPI and work life balance.